Initiating anticoagulant therapy after ICH is associated with patient characteristics and treatment recommendations - Sembill, Jochen; Wieser, Claudia; Sprügel, Maximilian; Gerner, Stefan; Giede-Jeppe, Antje; Reindl, Caroline; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Neurology, 2018)
The proportion of patients with intracerebral hemorrhage (ICH) and concomitant indication for oral anticoagulant (OAC) therapy is increasing. Although recent studies documented a favorable risk-benefit profile of OAC initiation, deciding whether, when, and which OAC should be started remains controversial. We investigated (1) OAC recommendations, its implementation, and adherence and (2) factors associated with OAC initiation after ICH. This prospective observational study analyzed consecutive ICH patients (n = 246) treated at the neurological and neurosurgical department of the University-Hospital Erlangen, Germany over a 21-month inclusion period (05/2013-01/2015). We analyzed the influence of patient characteristics, in-hospital measures, and functional status on treatment recommendations and on OAC initiation during 12-month follow-up. In-hospital mortality of 24.8% (n = 61/246) left 185 patients discharged alive of which 34.1% (n = 63/185) had OAC indication. In these patients, OAC initiation was clearly recommended in only 49.2% (n = 31/63) and associated with favorable [modified Rankin Scale (mRS) = 0-3] functional discharge status [OR 7.18, CI (1.05-49.13), p = 0.04], less frequent heart failure [OR 0.19, CI (0.05-0.71), p = 0.01], and younger age [OR 0.95, CI (0.90-1.00), p = 0.05]. OAC was more often started if clearly recommended [n = 19/31 (61.3%) versus (no recommendation) n = 4/26 (15.4%), p < 0.001; (clearly not recommended, n = 6)] and associated with younger age [67 (58-74) versus 79 (73-83), p < 0.001], favorable functional outcome [n = 10/23 (43.5%) versus n = 5/40 (12.5%), p = 0.01], decreased mortality [n = 6/23 (26.1%) versus n = 19/40 (47.5%), p = 0.06], and functional improvement [n = 13/17 (76.5%) versus n = 7/21 (33.3%), p = 0.01]. We observed no differences in rates of intracranial complications [thromboembolism, n = 3/23 (13.0%) versus n = 4/40 (10.0%), p = 1.00; hemorrhage, n = 1/23 (4.3%) versus n = 3/40 (7.5%), p = 1.00]. Clear treatment recommendations by attending stroke physicians significantly influence OAC initiation after ICH. OAC were more frequently recommended and started in younger patients with better functional recovery independent from intracranial complications. This might represent an important determinant of observed beneficial associations, hinting towards an indication bias which might affect observational analyses.
EVALuna2:34916